Effects of vitamin B3 supplementation on NAD+ biosynthesis and mitochondrial metabolism in human muscle and white adipose tissue - Kuusela, Minna (My University, 2020)
The complex pathophysiology of obesity-related disturbances is closely linked to mitochondria malfunction. Therefore, boosting mitochondrial activity could protect from metabolic complications. Based on animal studies, an effective way to achieve this and thus to improve metabolic health, is to activate the nicotinamide adenine dinucleotide (NAD+)/sirtuin pathway by NAD+ precursor nicotinamide riboside (NR, a vitamin B3 form) supplementation. However, long-term effects of NR have not been investigated at tissue level in obese subjects that have defective NAD+ biosynthesis. The primary objective of this MA thesis study was to elucidate the effects of NR on muscle and white adipose tissue (WAT) mitochondrial biogenesis and NAD+ biosynthesis, and investigate how initial body weight and genotype affect the baseline gene expression and response to NR in BMI-discordant monozygotic twins. Secondary objective of this study was to determine whether cultured primary muscle cells retain the mitochondria related phenotype of their tissue of the origin. To investigate these questions, a 5-month intervention with NR was performed in 16 BMI-discordant monozygotic twin pairs. Blood, muscle and WAT biopsies were collected before and after the intervention. Part of the muscle tissue sample was used for primary muscle cell cultures. Thereafter, mitochondrial DNA amount and the expression of genes associated with NAD+ biosynthesis and mitochondrial biogenesis pathways were determined with quantitative PCR and reverse transcription quantitative PCR, respectively. In this MA thesis, I will review results and conclusions based on aforementioned analyses.
Keywords: vitamin B3, obesity, nicotinamide riboside, mitochondrion, mitochondrial dysfunction, muscle, white adipose tissue, NAD+, NAD+ booster, sirtuin